Physiological temperature during brain slicing enhances the quality of acute slice preparations - Huang, Shiwei; Uusisaari, Marylka Y. (Frontiers in Cellular Neuroscience, 2013)
We demonstrate that brain dissection and slicing using solutions warmed to near-physiological temperature (~ +34˚C), greatly enhance slice quality without affecting intrinsic electrophysiological properties of the neurons. Improved slice quality is seen not only when using young (< 1 month), but also mature (>2.5 month) mice. This allows easy in vitro patch-clamp experimentation using adult deep cerebellar nuclear slices, which until now have been considered very difficult. As proof of the concept, we compare intrinsic properties of cerebellar nuclear neurons in juvenile (< 1 month) and adult (up to 7 months) mice, and confirm that no significant developmental changes occur after the fourth postnatal week. The enhanced quality of brain slices from old animals facilitates experimentation on age-related disorders as well as optogenetic studies requiring long transfection periods.